1989
DOI: 10.1007/bf02661807
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and surfactant properties of diglycerol esters of fatty acids

Abstract: Fatty acid mono‐ and diesters of diglycerol constitute the major portion of commercial polyglycerol esters; hence, their composition influences the performance of the latter as emulsifiers. The correlation of structure of the fatty acids in the mono‐ and diesters with surfactant properties is of interest. Linear diglycerol was isolated from polymerized glycerol by acetonation, fractional distillation and regeneration. Diglycerol mono‐ and diesters of undecenoic, lauric, stearic, oleic and ricinoleic acids were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
1
14
0
2
Order By: Relevance
“…Analysis results are shown in Table 1. The resulting 1 H NMR and the mass spectra of 2GML were the same as those reported earlier (7,8).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Analysis results are shown in Table 1. The resulting 1 H NMR and the mass spectra of 2GML were the same as those reported earlier (7,8).…”
Section: Resultssupporting
confidence: 55%
“…A cylinder with an internal diameter of 50 mm was used for foam property measurements; measurements were repeated three to four times. The respective mean values were evaluated, and the ratio of foam height at 5 min to the initial foam height was defined as foam stability (7,8,12).…”
mentioning
confidence: 99%
“…Atualmente, o glicerol derivado da indústria petroquímica (que apresenta alta pureza) é empregado na produção de cosméticos [10,11] , fármacos [12] , bronzeadores [13] , aditivos alimentares [10,11] e estabilizante para PVC [14] , aplicações que não são facilmente acessíveis para o glicerol derivado do biodiesel (que apresenta grau de pureza variável) [15] .…”
Section: Introductionunclassified
“…E nas regiões próximas às usinas de biodiesel, em 2009, o preço não ultrapassou R$ 700 t -1 [8] . Diante dessa situação, torna-se estratégico o desenvolvimento de novos processos para a conversão de glicerol em produtos de maior valor agregado [9] , pois a produção e mercado de glicerol, derivado da indústria petroquímica, já são estáveis.Atualmente, o glicerol derivado da indústria petroquímica (que apresenta alta pureza) é empregado na produção de cosméticos [10,11] , fármacos [12] , bronzeadores [13] , aditivos alimentares [10,11] e estabilizante para PVC [14] , aplicações que não são facilmente acessíveis para o glicerol derivado do biodiesel (que apresenta grau de pureza variável) [15] .Uma alternativa de transformação química, entre diversas descritas na literatura [15][16][17][18][19][20][21][22][23][24][25] , para consumir parte desse glicerol derivado do biodiesel é a reação de polimerização (Figura 2), pois os polímeros produzidos podem ter diferentes aplicações, tais como substitutos de polióis, e.g. álcool polivinílico [26] , aditivos para tintas [10] , lubrificantes [27] , aditivos para cimentos [4,28] e matéria-prima para produção de poliuretanas e resinas [12] de aplicações pouco nobres.…”
unclassified
“…At higher concentration and at temperatures over the Kraftt point, the emulsifier in water will exhibit mesomorphism forming different lyotropic phases, i.e. For a series of diglycerolesters of increasing acyl chain length, the surface tensions between water/air have been recorded by Kumar et al [26] and it is observed that the increasing chain length increases the surface tension. The polyglycerol ester will self-aggregate with the hydrophilic polyglycerol moiety oriented towards the surrounding water, and the fatty hydrocarbon chain packed in a more or less ordered form, away from the water.…”
Section: Phase Behaviourmentioning
confidence: 99%